FUEL WOOD CONSUMPTION: A MATTER OF CHOICE OR ECONOMICALLY CONSTRAINT ALTERNATIVE; AN ASSESSMENT OF ALTERNATIVE ENERGY PREFERENCES IN GOMBE METROPOLIS - Charles Ayuk, Nsor,; Abiram Damara Dorcas, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
The continuous dependence of human on fuel wood has resulted in serious degradation of the fragile forest ecosystem. We evaluated the scale of fuel wood usage as well as preference for other alternative sources of fuel and energy within the study area. We investigated the ecological implications of over-dependence on some preferred tree species that are harvested daily for use as fuel. Our results were drawn from Two hundred (200) structured questionnaires administered to willing respondents in the study area of Gombe metropolis and environs. Energy preference differed among household users, with (54.44 %) of 180 respondents favoring fuel wood, (17.22 %) gas, (10.56 %) kerosene, (10.56 %) electricity, (6.11 %) charcoal, and (1.11 %) preferred saw dust. Twenty (20) respondents drawn from bulk users were found to depend exclusively (100 %) on fuel wood. Anogeissus leiocarpus, Parkia biglobosa, and Detarium microcarpum were among the three most preferred and harvested of the nine known economic tree species recorded in this study, and may be the most vulnerable to local extinction in the near future. Affordability, availability and efficiency are the key drivers of fuel wood preference. Our results suggest that respondents prefer to use fuel wood exclusively rather than as an option. We found that conversion of woody tree species to fuel wood in the study area is unsustainable and unregulated, and pose severe consequences for biodiversity in Gombe and by extension the North – East region.